CommBo: Modernizing Augmentative and Alternative Communication. Issue 145 (January 2021) - Laxmidas, Kaveet; Avra, Cory; Wilcoxen, Christopher; Wallace, Michael; Spivey, Reed; Ray, Samantha; Polsley, Seth; Kohli, Puneet; Thompson, Julie; Hammond, Tracy
Highlights: Development of speech-generating Augmentative and Alternative Communication (AAC) tool. Emphasis on support for those with low-income or internet connectivity concerns. Interface adapts to user ability and preference and offers intelligent suggestions. Usability evaluated by three target users versus traditional methods using NASA TLX. Extended study with non-target users including function and design considerations. Abstract: For every 100, 000 people, there are 536 individuals with speech impairments who can benefit from the use of Augmentative and Alternative Communication (AAC) devices (Creer et al., 2016). Existing AAC devices can suffer from the shortcomings of being difficult to adjust to the user's specific needs or simply being expensive to own and maintain. We aim to reduce the impact of these problems with CommBo: a web-based, speech-generating picture communication board meant to alleviate some major difficulties commonly experienced by AAC users. CommBo offers customizability beyond that of a physical picture board and leverages machine learning to provide intelligent suggestions. It supports heightened communication that can be brought to a multitude of computing devices, including those that are low-cost or have limited internet access. CommBo is designed for those with autism spectrum disorder (ASD) and patients suffering from any trauma that impacts the person's ability to communicate effectively, e.g., stroke-induced aphasia. Across two studies, target and non-target participants evaluated CommBo in terms of functionality and usability, and results showed significant benefits of the system.